1985
DOI: 10.1159/000101138
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approach to the Pancoast Pain Syndrome

Abstract: The incidence of the Pancoast syndrome ranges from 2 to 5% of patients with lung cancer. We treated 20 cases between 1979 and 1984 with 29 procedures including percutaneous cordotomy, selective posterior radiculotomy, decompressive laminectomy, central administration of opiates, and TENS. Selective posterior radiculotomy gave the best pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the report by Loeser [10], the initial success rate was 54%, and the long-term success rate 43%, in 13 cancer pain patients. Esposito et al [8] reported their experience of cordotomy and selective posterior rhizotomy in 20 cases of the Pancoast syndrome, and posterior rhizotomy was effective in 14 of 16 patients at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the report by Loeser [10], the initial success rate was 54%, and the long-term success rate 43%, in 13 cancer pain patients. Esposito et al [8] reported their experience of cordotomy and selective posterior rhizotomy in 20 cases of the Pancoast syndrome, and posterior rhizotomy was effective in 14 of 16 patients at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal rhizotomy, first reported by Abbe [6] in 1911, involves sectioning of the posterior sensory rootlets and has been reported to have a role in patients in whom the specific dermatomal level can be identified [1,7,8,9,10,11,12,13,14,15,16]. According to a recent, detailed review of neuroablative treatment for cancer pain by Raslan et al [17], only cordotomy had some evidence of an effect among destructive procedures for cancer pain, and dorsal rhizotomy was said to have been abandoned for the open nature of its procedure, the fading effect and the presence of more effective procedures.…”
Section: Introductionmentioning
confidence: 99%
“…6 The operation involves the percutaneous insertion of an electrode through the cheek into the trigeminal nerve within Meckel's cave through the foramen ovale. [8][9][10][11][12][13] The use of this procedure for treating cancerrelated orofacial pain has not been reported in decades. The deliberately damaged nerve is then no longer able to transmit nociceptive signals.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques to interrupt pain pathways include multiple modalities 10 such as cervical cordotomy, 11,12 selective posterior rhizotomy/radiculotomy, 3 stereotactic thalamotomy, commissural myelotomy, and radiofrequency ablation; cervical epidural analgesia, 9 central administration of opiates, 3 and brachial plexus block 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Options for treating intractable pain in these patients include radiculotomy, cordotomy, and neuraxial administration of opiates. Selective posterior radiculotomy results in better pain relief than the latter 2 techniques 3 . Radiofrequency lesioning of the dorsal root ganglion can interrupt pain pathways in patients with intractable pain originating in the cervical nerve roots 4 .…”
Section: Introductionmentioning
confidence: 99%